Evaluationof compact air-induction flat fan nozzles for herbicide applications: Spray drift and biological efficacy - Wang, Shilin; Li, Xinjie; Nuyttens, David; Zhang, Lanting; Liu, Yajia; Li, Xue (Frontiers in Plant Science, 2023)
Nozzles are the most critical component of a sprayer for pesticide applications. Recently, air-induction nozzles and twin flat-fan air-induction nozzles have started to be used for herbicide applications. In order to evaluate the potential of compact air-induction nozzles for herbicide spraying, this paper compares the effects of air-induction nozzles and standard flat-fan nozzles on spray atomization, deposition, drift, and weed control efficacy in maize and wheat. Droplet spectra were measured by a laser particle size analyzer, and drift potential values were determined using a drift test bench (ISO 22401). A field study was conducted to compare the spray drift and biological efficacy between Lechler standard flat-fan nozzles and compact air-induction nozzles including different nozzle sizes. In the range from 0.2 to 0.4 MPa, the droplet size classes of the LU and ST nozzles were very similar and ranged from fine to very fine, while the droplets of the air-induction nozzles IDK and IDKT were medium or coarse depending on the spray pressure and nozzle size. The drift potential trials showed that the droplet size characteristics, mainly V100, are strongly linked with the drift reduction potential. Both drift potential and field results showed that the compact air-induction nozzles had a good performance in drift reduction. In terms of weed control biological efficacy, there were no significant differences between standard flat-fan nozzles and air-induction nozzles. In all cases, the efficacy values were above 80% both in maize and in wheat. In conclusion, air-induction nozzles are recommended for herbicide applications as they provide good biological efficacy while significantly reducing the amount of spray drift, which is of great significance for the protection of the environment and the surrounding sensitive crops.